Study Combination Vertical Wind Turbine in The Mining Area - RD. Kusumanto; Fatahul Arifin; Carlos R. S.; Dicky Septrianto; Rusdianasari; RM. Fauzi; Yusuf Dewantoro Herlambang (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
Wind Technology has developed rapidly because it is environmentally friendly alternative energy. The speed of the wind to run the wind turbine is able to exhaust a fan and ordinary wind sources. Tanjung Enim is one of Indonesia's areas, that have comparatively little wind energy. It has a wind velocity of 1.5 - 3 m/s. Tanjung Enim has coal mining, and the blower is used for air in the conveyor line of the mining. It is the potential to generate wind turbines. because the wind velocity in this area is 8 m /s. This study examines the enactment of blades on vertical wind turbines, namely Savonius with 3 blades combine with Darrius 3 blades. The result of the voltage output currently created by of vertical wind turbine maximum is 8.42 Volt and 345 Ampere.